Inside Back Cover: H2‐Fueled ATP Synthesis on an Electrode: Mimicking Cellular Respiration (Angew. Chem. Int. Ed. 21/2016). Issue 21 (12th May 2016) - Gutiérrez‐Sanz, Óscar; Natale, Paolo; Márquez, Ileana; Marques, Marta C.; Zacarias, Sonia; Pita, Marcos; Pereira, Inês A. C.; López‐Montero, Iván; De Lacey, Antonio L.; Vélez, Marisela
Abstract : The electrochemical oxidation of molecular H2 is coupled to the enzymatic synthesis of ATP. In their Communication onpage 6216 ff., A. L. De Lacey, M. Vélez, and co‐workers show that ATP synthesis is achieved by F1 F0 ‐ATP synthase immobilized within a lipid bilayer covering a gold electrode. The proton gradient across the membrane required for ATP synthesis is generated by the electro‐enzymatic oxidation of hydrogen gas performed by a bacterial hydrogenase also immobilized and oriented on the electrode.